1989
DOI: 10.1093/geronj/44.3.p61
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Caregiving Appraisal

Abstract: Caregivers of disabled older people were studied in terms of their appraisal of the caregiving process. A conceptual approach based on stress theory suggested that such appraisal was broader than the traditional term, "caregiving burden." An item pool was constructed using traditional and new items to represent dimensions of subjective caregiving burden, caregiving satisfaction, caregiving impact, caregiving mastery, and traditional caregiving ideology. Component analysis of responses of 632 caregivers in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
460
0
15

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 636 publications
(497 citation statements)
references
References 0 publications
22
460
0
15
Order By: Relevance
“…They also showed that most caregivers are unlikely to experience positive and negative experiences at the same moment, but in many individual caregivers a shift in the direction of their feelings, reactions and consequences of caregiving occurred. Lawton et al (1989) reported that caregiver satisfaction was not strongly related to burden. However, as mentioned before, research concerning positive aspects of cancer caregiving is in its infancy.…”
Section: Negative and Positive Aspects Of Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed that most caregivers are unlikely to experience positive and negative experiences at the same moment, but in many individual caregivers a shift in the direction of their feelings, reactions and consequences of caregiving occurred. Lawton et al (1989) reported that caregiver satisfaction was not strongly related to burden. However, as mentioned before, research concerning positive aspects of cancer caregiving is in its infancy.…”
Section: Negative and Positive Aspects Of Caregivingmentioning
confidence: 99%
“…Although most research has focused on negative experiences of giving care, more and more studies also report on the beneficial effects (Kinney and Stephens, 1989;Lawton et al, 1989;Motenko, 1989). There are several reasons to believe that experiences of caregiving can also be positive and that it might be worthwhile to investigate their effects on health.…”
Section: Negative and Positive Aspects Of Caregivingmentioning
confidence: 99%
“…A large number of family caregivers are helping relatives with medical and nursing tasks such as medication management, wound care, monitoring equipment (e.g., ventilators, feeding tubes, home dialysis units). Caregivers rarely receive adequate training to ensure they are able to (Lawton & Brody, 1969) and the Functional Independence Measure (Hamilton & Fuhrer, 1987 (Greene et al,1982) and the Caregiver Appraisal Questionnaire (Lawton et al, 1989). e. Overload 26 Schofield Measures objective and subjective caregiver burden by determining the occurrence of care experiences (i.e.…”
Section: Future Directionsmentioning
confidence: 99%
“…La plupart des premières recherches ont porté uniquement sur les aspects subjectifs et négatifs de l'aide. Dans un second temps, des auteurs ont proposé de tenir compte également des effets positifs [10,21,23,27,33,35]. Des entretiens, menés auprès de femmes âgées aidant à domicile leur époux souffrant de démence, ont montré que la perception d'une continuité dans la relation maritale entraîne un sentiment de gratification et de bien-être [33].…”
Section: Les éVolutions Des Mesures De Fardeauunclassified
“…Par ailleurs, le soutien effectif d'un entourage familial élargi, la présence d'amis ou de confidents sont autant de sources de reconnaissance de l'aidant [9]. Á la suite de ces travaux, plusieurs notions ont été utilisées pour comprendre le vécu des aidants : la satisfaction de vie [36], les bénéfices [23], la satisfaction et le sentiment de maîtrise [27]. Toutefois, les instruments qui en découlent sont majoritairement destinés aux aidants de personnes âgées dépendantes [27,36] ou de patients avec une altération cognitive [23,33].…”
Section: Les éVolutions Des Mesures De Fardeauunclassified